Bank liquidity and financial performance: evidence from Moroccan banking industry - Ferrouhi, El Mehdi (Business: Theory and Practice, 2014)
This paper aims to analyze the relationship between liquidity risk and financial performance of Moroccan banks and to define the determinants of bank’s performance in Morocco during the period 2001–2012. We first evaluate Moroccan banks’ liquidity positions through different liquidity and performance ratios then we apply a panel date regression to identify determinants of Moroccan banks performance. We use 4 bank’s performance ratios, 6 liquidity ratios and we analyze 5 specific determinants and 5 macroeconomic determinants of bank performance. Results show that Moroccan bank’s performance is mainly determined by 7 determinants: liquidity ratio, size of banks, logarithm of the total assets squared, external funding to total liabilities, share of own bank’s capital of the bank’s total assets, foreign direct investments, unemployment rate and the realization of the financial crisis variable. Banks’ performance depends positively on size of banks, on foreign direct investments and on the realization of the financial crisis and negatively on external funding to total liabilities, on share of own bank’s capital of the bank’s total assets and on unemployment rate while the dependence between bank performance and liquidity ratios and bank performance and logarithm of the total assets squared depend on the model used.